Does Spiritual Health Correlate With Breastfeeding Mother’s Self-Efficacy In The Sub-District Area? - Insi Farisa Desy Arya; Siti Aisyah; Elsa Pudji Setiawati; Nanan Sekarwana; Dida Akhmad Gurnida (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2022)
Spiritual health is an aspect that can provide motivation and purpose for someone to achieve their goals even in a difficult situation. One of the factors supporting the success of breastfeeding is the mother’s self-efficacy. Self-efficacy gives mothers confidence and strong motivation even in a difficult situation. This study aimed to determine the correlation between spiritual health and breastfeeding self-efficacy. This analytical correlational study used a cross-sectional approach. The study was conducted in October 2019 in Soreang Sub-district, Bandung Regency, one of the rural areas in Bandung Regency. The subjects of the study were chosen by cluster random sampling method and selected 52 subjects from 13 Posyandu in Soreang sub-districts. The primary data were obtained using instruments in the form of questionnaires. The level of the spiritual health of the subjects was obtained using Spiritual Health Inventory questionnaire. The level of breastfeeding self-efficacy of the subjects was obtained using the Breastfeeding Self-Efficacy Scale. Spearman rank correlation analysis indicated there is a correlation between spiritual health with breastfeeding self-efficacy, (p=0.029 r=0.303). According to the studied data, breastfeeding self-efficacy and spiritual health are correlated among breastfeeding mothers in Soreang Sub-district.